Production potential and economics of sesamum-pulse intercropping In Onattukara Tract - Bindhu J S (Department of Agronomy, College of Agriculture, 1999)
An experiment entitled "Production potential and economics of sesamum-pulse intercropping in Onattukara tract" was conducted in the summer rice fallows of Rice Research Station, Kayamkulam from February 1998 to August 1998. The study also aims at estimating the residual effect of the intercropping on succeeding crop of rice during virippu season. The experiment was laid out In randomised block design with nine treatments in four replications. The weather condition during the cropping period was congenial for crop growth. The treatments were sole crops of sesamum, blackgram and greengram, intercropping of sesamum with blackgram and greengram in 1: 1, 2: 1 and 3: 1 ratios. The results indicated that sesamum in general, having a tall growing habit was least affected by shade when put under intercropping systems with pulses under different planting ratios. The association of sesamum had lesser adverse effect on legumes and it was proved that legumes can be grown in a compatible manner with sesamum. The sole crops produced significantly higher seed yield than the intercropping systems, in which yield varied due to differences in